2017
DOI: 10.4236/ojog.2017.77068
|View full text |Cite
|
Sign up to set email alerts
|

A Theory-Based Dietary Intervention for Overweight, Postpartum Mothers and Their Children Improves Maternal Vegetable Intake

Abstract: Objective: To evaluate the effectiveness of a dietary intervention to increase target vegetable intake in overweight, postpartum mothers; and their children. Methods: Overweight mothers attending their six-week postpartum follow-up visit and their infants (n = 104 pairs) were randomized to intervention or usual care groups during the time period 2008-2011. Mothers received four 60 minute education sessions with a nutrition professional and eight monthly follow-up phone calls. Counseling began at the obstetrici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The characteristics of the trials are summarised in Table 2 . The eighteen studies ( n = 2559) are divided into three categories according to the timing of the intervention: pregnancy only ( n = 3) [ 35 , 36 , 37 ], pregnancy and postpartum ( n = 3) [ 38 , 39 , 40 ] or postpartum only ( n = 12) [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The characteristics of the trials are summarised in Table 2 . The eighteen studies ( n = 2559) are divided into three categories according to the timing of the intervention: pregnancy only ( n = 3) [ 35 , 36 , 37 ], pregnancy and postpartum ( n = 3) [ 38 , 39 , 40 ] or postpartum only ( n = 12) [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the studies aimed to reduce postpartum weight ( n = 14) [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 43 , 45 , 46 , 47 , 49 , 50 , 51 ], three studies aimed to improve diet quality [ 42 , 44 , 52 ] and one trial aimed to determine whether weight loss affected infant growth [ 48 ]. In those studies where the assessment of postpartum weight management was not included as a primary aim, it was reported as a secondary outcome [ 42 , 44 , 48 , 52 ]. All trials initiated during pregnancy ( n = 6) reported changes in weight from pre-pregnancy weight to 6 [ 35 , 37 , 39 , 40 ] and/or 12 months postpartum [ 36 , 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations